2013
DOI: 10.4254/wjh.v5.i8.425
|View full text |Cite
|
Sign up to set email alerts
|

Participation of peribiliary glands in biliary tract pathophysiologies

Abstract: AIM:To investigate the roles of peribiliary glands around the bile ducts in the pathophysiology of the biliary tract. METHODS:The expression of fetal pancreatic markers, pancreatic duodenal homeobox factor 1 (PDX1) and hairy and enhancer of split 1 (HES1) and endodermal stem/progenitor (S/P) cell markers [CD44s, chemokine receptor type 4 (CXCR4), SOX9 and epithelial cell adhesion molecule (EpCAM)] were examined immunohistochemically in 32 normal adult livers (autopsy livers) and 22 hepatolithiatic livers (surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…; Igarashi et al. ), but our results also suggest that PDGs are candidate sites of origin of pancreatic intra‐epithelial neoplasias (PanIN) and pancreatic duct adenocarcinomas. Also, in response to injury, PDGs undergo a mucinous metaplasia with PanIN features (Strobel et al.…”
Section: Discussionsupporting
confidence: 65%
“…; Igarashi et al. ), but our results also suggest that PDGs are candidate sites of origin of pancreatic intra‐epithelial neoplasias (PanIN) and pancreatic duct adenocarcinomas. Also, in response to injury, PDGs undergo a mucinous metaplasia with PanIN features (Strobel et al.…”
Section: Discussionsupporting
confidence: 65%
“…In IgG4-related sclerosing cholangitis, focal or multifocal biliary strictures are most commonly seen in the distal common bile duct and hilar and central intrahepatic bile ducts. This imaging feature correlates with the abundance of peribiliary glands in these locations at histopathologic examination (5). Patients with type 1 autoimmune pancreatitis may also occasionally demonstrate focal or multifocal pancreatic ductal strictures, ectatic side branches arising from the site of the stricture, and a lack of upstream ductal dilatation (25,26).…”
Section: Inflammatory Diseasesmentioning
confidence: 83%
“…Thus, the biliary tract acts as a conduit for the secretions from the hepatic parenchyma (bile) and from the peribiliary glands. The peribiliary glands can be located within the bile duct wall (intramural type) or the periductal connective tissue (extramural type) (Fig 1) (5,6). Although intramural peribiliary glands are simple tubular mucous glands, extramural peribiliary glands are branched tubuloalveolar seromucous glands.…”
Section: Teaching Pointsmentioning
confidence: 99%
“…(15) However, over the past decade, PBG cells have been characterized in more detail and stem cell properties of PBG have come to light. (1,3,16,17) Although marked proliferation of PBG in the context of large bile duct pathologies has been described for hepatolithiasis, for primary sclerosing cholangitis, and after ischemia, (4)(5)(6) today's view on PBG and their counterparts in the pancreas and liver suggests that several other hepato-pancreato-biliary diseases are also linked with these progenitor cell compartments. (2,18,19) In support of this, the current ex vivo study demonstrated the central role of PBG in bile duct recovery after severe ischemic damage.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the activation of PBG has been observed in patients with hepatolithiasis, primary sclerosing cholangitis, and posttransplant cholangiopathies. (3)(4)(5)(6) Our understanding of PBG and their behavior in pathological conditions is based on findings in cross-sectional studies, animal studies, and cell cultures. These models have not provided definite proof of the functional and morphological recovery of the biliary epithelial lining by a coordinated response of PBG cells after severe injury of the large bile ducts in humans.…”
mentioning
confidence: 99%